Analysis of the role of Islamic religious education in the formation of adolescent character - Wieke, Erzy Asty; Lestari, Desi; Hadi, Zamarul; Yuriska, Yuriska; Nuraini, Putri; Muslimah, Umi; Hasibuan, Amin Rais (Cendikia : Media Jurnal Ilmiah Pendidikan, 2025)
Islamic Religious Education (PAI) plays a crucial role in shaping the character of adolescents, especially amidst the moral challenges faced by the younger generation today. This study aims to explore how PAI can shape character based on Islamic values through a holistic approach in various environments, including family, school and community. A descriptive qualitative method was used to analyze the data obtained from the literature study. The results show that PAI include the integration of Islamic values in the curriculum, habituation of worship, as well as exemplary behavior from teachers and parents. This study emphasizes the importance of innovation in learning methods so that PAI remains relevant and effective in shaping adolescent character in the digital era.